Structural optimization and finite element analysis of poly‐l‐lactide acid coronary stent with improved radial strength and acute recoil rate. Issue 7 (10th March 2020) - Song, Kai; Bi, Yuying; Zhao, Haibin; Wu, Tim; Xu, Feng; Zhao, Guoqun
Abstract: Current poly‐l ‐lactide acid (PLLA) scaffolds have issues of inadequate mechanical strength leading to thrombosis formation. Designing a novel bioabsorbable PLLA stent with a novel structure and improved mechanical property is urgently needed. In this study, stent structure modification and optimization based on bioresorbable vascular scaffold Version 1.1 (BVS 1.1, Abbott Laboratories) were conducted. The mechanical property of the redesigned stent was studied using both computerized finite element analysis and experimental mechanical deformation testing, including radial strength (RS), acute recoil (AR), foreshortening (FS), and bending stiffness (BS). The simulated and experimental results showed that the mechanical properties of the modified structure were significantly improved (modified stent vs. BVS 1.1: RS: 2.25 vs. 1.29 N/mm; AR: 3.03 vs. 4.41%; FS: 1.13 vs. 6.89%; BS: 1.49 vs. 0.72 N mm 2 ).